"Deliver Me From This Indignity!": Cottage Hospitals, Localism and NHS Healthcare in Central England, 1948-1978. (2nd July 2016) - Hurren, Elizabeth T.
Abstract : Victorian and Edwardian cottage hospitals, compared to infirmaries and workhouse institutions, have been neglected by social historians. Yet, they provided an infrastructure dedicated to localism and healthcare for the aged under the new National Health Service (NHS) after World War Two. This article focuses on two renowned Midlands cottage hospitals built in mid - Northamptonshire at Pitsford. In their patient case - histories we can engage with: dignity standards, medical regime, ward designs, staffing levels, budget provisions, and patient voices. These popular institutions had a well - deserved reputation for delivering high - quality geriatric medicine from 1948 to 1978. Human vignettes detailing the physical indignities of ageing nonetheless proliferate in the records. The longevity of these basic issues was to prove to be a recurring tension in NHS financial planning. Budget models lacked enough funds for aged patients to receive 'stable' bedside care. Instead, NHS accountants allocated resources to ensure the future 'sustainability' of the system itself. A new paradigm highlights the inherent financial contradictions and empty political promises that those needing geriatric care often experienced, and still do. Throughout, the rediscovered cottage hospital records contain important historical lessons for the present impasse about how to define, deliver and secure dignity for elderly patients in today's NHS.